A cross sectional study of organizational factors and their impact on job satisfaction and emotional burnout in a group of Australian nurses: infection control practitioners - Katie Page; Nicholas Graves (BMC, 2021)
Abstract Background Infection control practitioners (ICPs) are a group of specialized nurses fundamental to effective healthcare infection prevention and control initiatives. Relative to other groups of nurses much less is known about their working conditions. Organizational factors may impact ICPs' levels of job dissatisfaction and emotional job burnout and, subsequently, their quality of practice. We measure a range of organizational factors to document the working conditions of ICPs and show how these are linked to job satisfaction and emotional burnout in a sample of Australian ICPs. Methods We conducted a cross sectional study using an online survey. All employed ICPs in 50 of the largest public hospitals in Australia were invited to participate. One hundred and fifty three ICPs completed the survey. Results ICPs are moderately to highly satisfied with their job but show high levels of emotional burnout, time pressure and cognitive demands. Low job satisfaction was associated with less job control, low perceived organizational support and poor communication. In contrast, emotional burnout was associated with high time pressure and cognitive demands coupled with poor communication. Discussion This study provides new evidence about the organizational context of ICPs in Australia, and about the factors that impact on job satisfaction and emotional burnout. These findings may be used to modify national infection prevention and control programs to suit local organizational contexts. Further research is needed to determine the precise nature of these relationships and the downstream impacts on hospital-wide infection control outcomes. Conclusions Organizational context and factors are important to consider when evaluating the impact and implementation of infection control programs.